Determining the optimal threonine:lysine ratio for the 25 to 50 lb pig - J R Bergstrom; J A Loughmiller; R E Musser; W B Nessmith Jr; Jim L Nelssen; Michael D Tokach; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1996)
A 21-day growth trial was conducted to determine the threonine: lysine ratio necessary to optimize growth performance of the 25 to 50 Ib pig reared in a high-health, segregated early-weaning (SEW) system. Ten experimental diets, including two levels of lysine (.75% and 1.10% apparent digestible lysine) and five apparent digestible threonine:lysine ratios (40, 47.5, 55, 62.5, and 70%), were used in a 2 x 5 factorial arrangement. Growth performance was improved by feeding 1.10% rather than.75% digestible lysine. Also, results indicated that the apparent digestible threonine requirement for the SEW:-reared, 25 to 50 lb pig is approximately 55% of digestible lysine.; Swine Day, Manhattan, KS, November 21, 1996
Keywords: Swine day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 772; Swine; Early-weaned pigs; Amino acids; Threonine